IYYAKA NA’BUDU PERSPEKTIF PENDIDIKAN ISLAM - Rudi Ahmad Suryadi (Universitas Pendidikan Indonesia, 2021)
AbstractEducation in an Islamic perspective directs humans to be close to Allah SWT. Swt. This closeness is built through a process of worship. This is because humans are seen as His servants. Education has a noble task, which is to lead people to realize their life's duties, namely worshiping Allah SWT. The purpose of education as the direction and determinant of the educational process, should be oriented towards forming a human being a servant of Allah SWT. who are obedient and obedient to His rules. As a servant of Allah SWT., All of his efforts and activities must be carried out in order to worship Allah SWT. To be able to carry out his life duties, namely worship, humans need to be provided with education, teaching, experience and skills, technology and other supporting facilities. This shows that the concept of worship in the Qur'an is closely related to education.Keywords: Islamic Education, Worship, al-Qur’an AbstrakPendidikan dalam perspektif Islam mengarahkan manusia untuk dekat dengan Allah Swt. Swt. Kedekatan tersebut dibangun melalui proses ibadah. Sebab, manusia dipandang sebagai hamba-Nya. Pendidikan mempunyai tugas yang mulia yaitu mengantarkan manusia untuk menyadari akan tugas hidupnya, yaitu beribadah kepada Allah Swt. Tujuan pendidikan sebagai arah dan penentu proses pendidikan, hendaknya berorientasi pada pembentukan seorang manusia menjadi hamba Allah Swt. yang taat dan patuh pada aturan-Nya. Sebagai seorang hamba Allah Swt., seluruh usaha dan aktivitasnya harus dilaksanakan dalam rangka beribadah kepada Allah Swt. Untuk dapat melaksanakan tugas hidupnya tersebut, yaitu ibadah, manusia perlu diberikan pendidikan, pengajaran, pengalaman, dan keterampilan, teknologi, dan sarana pendukung lainnya. Hal ini menunjukkan bahwa konsep ibadah dalam Al-Qur’an berkaitan erat dengan pendidikan.Kata Kunci: Pendidikan Islam, Penghambaan, Alquran